Skeletal muscle reference for Chinese children and adolescents. Issue 1 (30th November 2018) - Liu, Junting; Yan, Yinkun; Xi, Bo; Huang, Guimin; Mi, Jie; ,
Abstract: Background: Skeletal muscle as an essential body composition component plays an important role in maintenance of normal growth and development as well as systemic glucose metabolism in children. No nationwide reference data for skeletal muscle mass for Chinese youths are available in China. We aimed to establish the sex‐specific and age‐specific percentile reference values of skeletal muscle mass for Chinese children and adolescents. Methods: This study consisted of 10 818 children and adolescents aged 3–17 years in Chinese urban area during 2013–15. Dual‐energy X‐ray absorptiometry scan was performed to measure whole body muscle mass and appendicular skeletal muscle mass. Lambda‐mu‐sigma method was used to obtain the sex‐specific and age‐specific percentile curves of muscle mass indices. Results: Overall, whole body muscle mass and appendicular skeletal muscle mass indices showed an increasing trend with age for both sexes, with boys vs. girls having higher values of all muscle mass indices. Whole body muscle mass index in boys increased slightly before age 9 years and then increased rapidly until 15 years and slowed down thereafter, while the mean values in girls increased slightly before age 8 years, increased rapidly until 14 years and remained stable thereafter. Appendicular skeletal muscle mass index increased rapidly until age 16 years and then increased slightly for boys; by contrast, for girls, the mean values increased consistently before age 14 years but showed a slightly decreasing trend after that. Conclusions: This study established sex‐specific and age‐specific percentile reference values for skeletal muscle mass for Chinese children and adolescents aged 3–17 years. These reference values can be used to evaluate the muscular development in Chinese children and adolescents.